Association of different domains of sedentary behavior and cardiovascular risk factors in adolescents: Cross-sectional study - Antunes, E. P. [UNESP]; Tebar, W. R. [UNESP]; Cucato, G. G.; Silva, C. C.M. [UNESP]; Leoci, I. [UNESP]; dos Santos, A. B. [UNESP]; Ferrari, G.; Christofaro, D. G.D. [UNESP] (Elsevier, 2024)
Background: Sedentary behavior (SB) has been related to cardiovascular risk factors (CVRF) such as high BMI, waist circumference (WC) and blood pressure (BP), including pediatric populations. However, it is still unclear whether the association between SB and CVRF could be domain dependent. Therefore, this study aimed to analyze the relationship between sedentary at different domains (time spent in TV, videogames, computer, smartphone) with CVRF in adolescents. Methods: A sample of 1011 adolescents (10–17 years old; 55.1% girls) was assessed. The different BS domains were obtained through a questionnaire, as well as socioeconomic status, habitual physical activity, smoking and alcohol consumption. BMI was calculated by objectively measured height and body mass, WC was assessed at middle point between the last rib and iliac crest, and BP was assessed by a digital oscillometric device. The relationship between SB and CVRF was determined by quantile regression, adjusted for sex, age, socioeconomic status, physical activity, smoking and alcohol consumption. Results: Elevated time in smartphone use was associated with higher median values of WC (β = 1.88; 95%CI: (0.27; 3.49) and SBP (β = 2.70; 95%CI: 0.35; 5.05). High total time spent in SB was associated with higher median values of BMI (β = 0.68; 95%CI = (0.02; 1.35), WC (β = 1.95; 95% = 0.47; 3.42) and SBP (β = 2.52; 95%CI: 0.37; 4.68). Conclusions: Smartphone use and total SB time were related to higher CVRF in adolescents. Cardiovascular health promotion strategies should focus on reducing SB in pediatric populations, especially smartphone use.
Asociación de diferentes dominios del comportamiento sedentario y factores de riesgo cardiovascular en los adolescentes: estudio transversal
Keywords: Cardiovascular health; Pediatric; Public health; Screen time; Youth